Religion and Society - Vettikuzhiyil, Roy (Asian Horizons, 2011)
Kurian Kachappilly, CMI, ed. Process, Religion and Society, Bangalore: Dharmaram Publications, 2009, Pages: 286, ISBN-978-81-89958-39-8